Parametric Modeling of Moisture Assisted Creep in Polymeric Composites - Upadhyay P.C.; Mishra A. (My University, 2025)
This paper is concerned with the development of a simple mechanical model for studying the effect of moisture absorption on the creep performance of polymeric composites. It is based on the application of Kelvin-Voight model generally used for viscoelastic materials. Moisture diffusion is assessed using a Fickean solution, and the property changes in composites due to moisture absorption are estimated using linear empirical relations. A parametric study has been performed to bring out the relative effects of material parameters, level of moisture, the elastic modulus, viscous modulus and the volume fraction (swelling) of the polymer due to moisture absorption. Results are pre sented with the help of non-dimensional plots of compliance variation with time. Since the material parameters are also expressed in non-dimensional form, findings and conclusions are not restricted to any particular composite. © 1994, Sage Publications. All rights reserved.